Significance of the buccal fat pad in oral surgery - Ostojic, Mihailo; Pejic, Maria; Orescanin, Miroslav; Vladimir Biocanin (Medicinski časopis, 2024)
Buccal fat pad (BFP) is used in oral and maxillofacial surgery for closing oroantral communications (OAC), closing larger oroantral and oronasal defects, repairing congenital clefts, covering bone grafts, temporomandibular joint surgery and in aesthetic surgery. In daily oral surgery practice, the use of a BFP to close the OAC is indicated when there is a fistula on the mucosa of the vestibule, wide communication in the distal parts of the edentulous alveolar ridge and wide OAC in the region of the third molar and in cases of prominent coronoid process of the lower jaw.